2017
DOI: 10.3390/catal7070204
|View full text |Cite
|
Sign up to set email alerts
|

Acidity-Reactivity Relationships in Catalytic Esterification over Ammonium Sulfate-Derived Sulfated Zirconia

Abstract: New insight was gained into the acidity-reactivity relationships of sulfated zirconia (SZ) catalysts prepared via (NH 4 ) 2 SO 4 impregnation of Zr(OH) 4 for propanoic acid esterification with methanol. A family of systematically related SZs was characterized by bulk and surface analyses including XRD, XPS, TGA-MS, N 2 porosimetry, temperature-programmed propylamine decomposition, and FTIR of adsorbed pyridine, as well as methylbutynol (MBOH) as a reactive probe molecule. Increasing surface sulfation induces a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(75 citation statements)
references
References 50 publications
0
75
0
Order By: Relevance
“…Figure shows the FTIR spectrum of pyridine adsorbed MIL‐101 and MIL‐101s and shows the nature of the acid sites (Brönsted and Lewis). Pyridine bound to Lewis acid sites gives characteristic vibrational bands at 1620–1604, 1580–1570, 1495–1485, and 1445–1440 cm −1 , whereas pyridine bound to Brönsted acid sites gives characteristic vibrational bands at 1640–1630, 1545–1535, and 1500–1485 cm −1 . In pyridine adsorbed MIL‐101, Lewis acid sites are identified due to the presence of Cr 3+ in the framework.…”
Section: Resultsmentioning
confidence: 99%
“…Figure shows the FTIR spectrum of pyridine adsorbed MIL‐101 and MIL‐101s and shows the nature of the acid sites (Brönsted and Lewis). Pyridine bound to Lewis acid sites gives characteristic vibrational bands at 1620–1604, 1580–1570, 1495–1485, and 1445–1440 cm −1 , whereas pyridine bound to Brönsted acid sites gives characteristic vibrational bands at 1640–1630, 1545–1535, and 1500–1485 cm −1 . In pyridine adsorbed MIL‐101, Lewis acid sites are identified due to the presence of Cr 3+ in the framework.…”
Section: Resultsmentioning
confidence: 99%
“…Acidity of SZ is dependent on the available sulfate ions, which are responsible for supplying H + ions during the reaction. It has been reported that at temperatures higher than 630 °C, sulfate ions are not stable in dynamic reaction conditions [34], and leave SZ surface in gaseous states (SO x ). Thus, SZ loses the required acidity to transform methyl radicals to aromatics like benzene and is similar to ZrO 2 , as observed from these runs.…”
Section: Activation Of Methanementioning
confidence: 99%
“…It has been reported that the sulfurized form of ZrO 2 known as sulfated zirconia (SZ), actively helps the active metal sites to stabilize on the oxide support at a greater degree [29,33]. SZ is a well-known solid acid possessing surface H + ions [29,34], which can react with some of the excess methyl radicals and remove these in the form of benzene and heavier hydrocarbons as valuable side products [15,35].…”
Section: Introductionmentioning
confidence: 99%
“…This advantage has resulted in the recent development of a wide range of solid acid catalysts to obtain biodiesel from various feedstocks. They include zeolites (Jeon et al, 2019;Osatiashtiani et al, 2017), clays (Bálsamo et al, 2019), metal oxides and mixed metal oxides (Pandit and Fulekar, 2019;Prabu et al, 2019), supported acids (Vieira et al, 2017;Aziz et al, 2017), sulphated metal oxides in particular sulphated zirconium oxide (H ≥ -14.52) (Shi et al, 2017;Elimbinzi et al, 2018;Rabee et al, 2017) and sulphated titanium oxide (H ≤-14.52) (Gardy et al, 2016(Gardy et al, , 2017, heteropoly compounds (Kurhade et al, 2019), sulfonated carbon based materials including carbon nanofibers; carbon nanotubes; biochar; amorphous carbon; graphene oxide; sugar; and waste (Guan et al, 2017;Tran et al, 2016;Baig et al, 2016;Tan et al, 2019;Bora et al, 2018;Rahimzadeh et al, 2018;Wu et al, 2019) and cation exchange resin (Zhang 2016;Fu et al, 2016).…”
Section: Solid Acid-catalyzed Transesterificationmentioning
confidence: 99%